A STUDY OF DUAL PHASE STEEL THROUGH HEAT TREATMENTS OF INTERMEDIATE QUENCHING AND INTERCRITICAL ANNEALING ON SS400 STEEL - Yusup Iskandar, Maulana
The rapid development of the automotive industry continuously demands improvements in various factors, such as safety, efficiency, and cost-effectiveness. Enhancements in these factors can be achieved by optimizing the materials used in vehicle construction. Dual-phase steel, produced through intercritical annealing heat treatment, is widely used in the automotive industry due to its strong, tough, and formable properties. SS400 steel, a low-carbon steel, is easily accessible and relatively inexpensive. By using cheaper raw materials and engineering their mechanical properties, production costs can be reduced, and efficiency can be improved without compromising safety. In this study, variations of normalizing, quenching, and intercritical annealing heat treatments were applied to SS400 steel to observe the microstructure and mechanical properties. The normalizing treatment was conducted at 870 °C with a 10-minute holding time, followed by air cooling. The specimens were then austenitized again at temperatures of 870 °C, 900 °C, and 930 °C for 10 minutes before being quenched. Subsequently, the specimens underwent intercritical annealing at 750 °C, 770 °C, and 800 °C. These were compared with conventional heat treatments at the same intercritical annealing temperatures. Characterization was carried out through tensile testing, Vickers hardness testing, metallography using an optical microscope, and fractography using SEM. Based on the characterization data, the effects on microstructure and mechanical properties were determined. The results showed that the obtained microstructure consisted of ferrite and martensite phases. There was a trend of increasing strength and hardness with rising austenitizing and intercritical annealing temperatures, reaching maximum values of 843.8 MPa and 331 HV at 930 °C austenitizing and 800 °C intercritical annealing. The maximum Charpy impact energy was obtained at 900 °C austenitizing and 750 °C intercritical annealing, with a value of 90,24 J/cm2. The maximum elongation was achieved at 870 °C austenitizing and 750 °C intercritical annealing, with a value of 26%. The fracture mechanism was a mixture of brittle and ductile fractures. The SS400 steel subjected to the heat treatments in this study successfully entered the region of 1st Gen Advanced High Strength Steel.